Le canabae legionis: aspetti giuridici della vita dei militari in provincia - Di Donato, Giuseppe (Cultura giuridica e diritto vivente, 2020)
[Canabae Legionis: Legal Aspects of Military Life in Province] This paper presents some data and research lines concerning the legal aspects of the ‘canabae legionis’, the civilian settlements which were often found near military garrisons: albeit numerous studies have been conducted on this particular issue, it is still surrounded by much uncertainty. The etymology of the term ‘canabae’ will also be explored, and its presence in legal, literary, and epigraphic sources.